2021
DOI: 10.3389/fpsyg.2021.629357
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Resilience Across Participating Regions in the UPRIGHT EU Horizon 2020 Project: Factor Structure and Psychometric Properties of the Resilience Scale for Adolescents

Abstract: Resilience is the process and outcome of healthy adaptation despite significant adversity. Proliferation of research on the resilience construct has led to scientific concerns about the operationalization and measurement of resilience for assessment science and practice. Various studies that have investigated the psychometric properties and construct validity of the Resilience Scale for Adolescents (READ) have yielded inconsistent findings, which could partly be due to variations in the methodological approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, the factorial validity of the READ has led to inconsistent results. A cross-country validation showed that the five-factor model was similar in adolescents aged 10–15 years from four European countries (Spain, Iceland, Italy, Poland) [ 28 ], whereas other studies showed problematic items loading, and were able to retain five-factor solution only after removing a number of items (e.g., 26 items [ 29 ], 23 items [ 30 ], and 20 items [ 16 ]). The factors of the READ have been proven to have a Cronbach’s alpha ranging from 0.69 for the ‘structured style’ factor till 0.89 for the ’family cohesion’ factor [ 16 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the factorial validity of the READ has led to inconsistent results. A cross-country validation showed that the five-factor model was similar in adolescents aged 10–15 years from four European countries (Spain, Iceland, Italy, Poland) [ 28 ], whereas other studies showed problematic items loading, and were able to retain five-factor solution only after removing a number of items (e.g., 26 items [ 29 ], 23 items [ 30 ], and 20 items [ 16 ]). The factors of the READ have been proven to have a Cronbach’s alpha ranging from 0.69 for the ‘structured style’ factor till 0.89 for the ’family cohesion’ factor [ 16 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while negative life events, like the divorce of one’s parents or the death of a loved one, are associated with lower scores on the READ scale, one’s engagement in hobbies, such as sports, correlates with higher READ scores [ 34 ]. Overall, the psychometric properties of the READ have been verified in various countries and languages, including Italian [ 32 ], German [ 35 ], Spanish [ 29 , 36 ], Icelandic, and Polish [ 28 ]. However, no Arabic version has been made available to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation